2011
DOI: 10.1002/jbm.a.33245
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural analysis of implant–soft tissue interface on a three dimensional tissue‐engineered oral mucosal model

Abstract: A three dimensional tissue-engineered human oral mucosal model (3D OMM) used in the investigation of implant-soft tissue interface was recently reported. The aim of this study was to examine the ultrastructural features of soft tissue attachment to various titanium (Ti) implant surfaces based on the 3D OMM. Two techniques, that is, focus ion beam (FIB) and electropolishing techniques were used to prepare specimens for transmission electron microscopic (TEM) analysis of the interface. The 3D OM consisting of bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…[1][2][3]6 Titanium (Ti) has been widely used as abutment material due to its superior corrosion resistance, high strengthto-weight ratio, and biocompatibility. 2,7 Studies have shown evidence of soft tissue attachment to the Ti surfaces, 8,9 which could form a biological seal around the implant. 10 Various Ti surface modifications to optimize the soft tissue attachment on the Ti abutments have been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3]6 Titanium (Ti) has been widely used as abutment material due to its superior corrosion resistance, high strengthto-weight ratio, and biocompatibility. 2,7 Studies have shown evidence of soft tissue attachment to the Ti surfaces, 8,9 which could form a biological seal around the implant. 10 Various Ti surface modifications to optimize the soft tissue attachment on the Ti abutments have been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been suggested that the quality of the BS of peri-implant tissue is weaker than that of the junctional epithelium on the natural teeth [1,5,6]. This could be due to the attachment of the non-keratinized periimplant epithelium (PIE) onto the implant surface via the internal basal lamina, hemidesmosomes [5,7] being limited to the apical region of the PIE [5]. In addition, the orientation of the peri-implant connective tissue collagen fibres, which are mainly in a circular or oblique direction to the implant surface [8,9], forms a weaker barrier compared with the Sharphey's fibres that attach perpendicular to the tooth surface [10].…”
Section: Introductionmentioning
confidence: 99%
“…We have developed and optimized an in vitro threedimensional oral mucosal model (3D OMM) for biological evaluation of dental materials and oral healthcare products [16][17][18] and more recently have modified it into a transmucosal implant model for the investigation of the implant -soft tissue interface [7,19]. The threedimensional transmucosal model is a tissue-engineered oral mucosa equivalent (OME) consisting of both epithelium and connective tissue layers.…”
Section: Introductionmentioning
confidence: 99%
“…It was also shown by TEM examination of ultrathin (electropolished) sections that the cells grew into the irregular and porous surfaces. Furthermore, the evidence of hemidesmosome-like structure formation on titanium surface topographies have been reported [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The 3D in vitro model enabled examination of the implant–soft tissue interface using several qualitative and quantitative biological endpoints, including basic histology using light microscopy (LM), ultrastructural analysis by scanning electron microscopy (SEM) and transmission electron microscopy (TEM) [ 14 ], confocal laser scanning microscopy (CLSM), a soft tissue–implant adhesion test [ 10 ], contour analysis of the implant–soft tissue interface [ 13 ], and measurement of the biological seal of implant–soft tissue interface [ 12 ].…”
Section: Introductionmentioning
confidence: 99%